Cardiac and cardiometabolic phenotyping of trastuzumab-mediated cardiotoxicity: a secondary analysis of the MANTICORE trial. Issue 2 (19th February 2021) - Kirkham, Amy A; Pituskin, Edith; Thompson, Richard B; Mackey, John R; Koshman, Sheri L; Jassal, Davinder; Pitz, Marshall; Haykowsky, Mark J; Pagano, Joseph J; Chow, Kelvin; Tsui, Albert K; Ezekowitz, Justin A; et al.
Abstract: Aims: An improved understanding of the pathophysiology of trastuzumab-mediated cardiotoxicity is required to improve outcomes of patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer. We aimed to characterize the cardiac and cardiometabolic phenotype of trastuzumab-mediated toxicity and potential interactions with cardiac pharmacotherapy. Methods and results: This study was an analysis of serial magnetic resonance imaging (MRI) and circulating biomarker data acquired from patients with HER2-positive early-stage breast cancer participating in a randomized-controlled clinical trial for the pharmaco-prevention of trastuzumab-associated cardiotoxicity. Circulating biomarkers (B-type natriuretic peptide, troponin I, MMP-2 and -9, GDF-15, neuregulin-1, and IGF-1) and MRI of cardiac structure and function and abdominal fat distribution were acquired prior to trastuzumab, post-cycle 4 and post-cycle 17. Ninety-four participants (51 ± 8 years) completed the study with 30 on placebo, 33 on perindopril, and 31 on bisoprolol. Post-cycle 4, global longitudinal strain deteriorated from baseline in both placebo (+2.0 ± 2.7%, P  = 0.002) and perindopril (+0.9 ± 2.5%, P  = 0.04), but not with bisoprolol (−0.2 ± 2.1%, P  = 0.55). In all groups combined, extracellular volume fraction and GDF-15 increased post-cycle 4 (+1.3 ± 4.4%, P  = 0.004; +130 ± 150%, P  ≤ 0.001, respectively). However, no significant change in troponin I was detected throughout trastuzumab. In all groups combined, visceral and intermuscular fat volume increased post-cycle 4 (+7 ± 17%, P  = 0.02, +8 ± 23%, P  = 0.02, respectively), while muscle volume and IGF-1 decreased from post-cycle 4 to 17 (−2 ± 10%, P  = 0.008, -18 ± 28%, P  < 0.001, respectively). Conclusion: Trastuzumab results in impaired cardiac function and early myocardial inflammation. Trastuzumab is also associated with deleterious changes to the cardiometabolic phenotype which may contribute to the increased cardiovascular risk in this population.